Influencing Factors of Insulin Resistance in Polycystic Ovary Syndrome Patients with Normal Body Mass Index - LUO Rong, WANG Yu, MIAO Afeng, WU Xiaoke (Zhongguo quanke yixue, 2023)
Background The incidence of insulin resistance (IR) is higher in patients with polycystic ovary syndrome (PCOS) regardless of whether they are obese, which seriously affects their reproductive and metabolic health. At present, there are few studies on the influencing factors of IR in PCOS patients with normal body mass index (BMI) . Objective To explore the influencing factors of IR in PCOS patients with normal BMI. Methods This study was a secondary analysis based on the clinical trial of the Effect of Acupuncture and Clomiphene Citrate on Live Birth in Infertile Women with PCOS (PCOSAct) , which was a multicenter, large-sample randomized controlled trial conducted in Chinese from 2011 to 2015, involving 1 000 PCOS infertile participants with fertility demand from 27 hospitals in the sub-centers, among whom 453 with normal BMI (18.5 kg/m2<BMI<24.0 kg/m2) were included in this study. The demographic characteristics, sex hormones, glucose and lipid metabolism, liver and kidney functions, and electrolytes were compared between patients with IR〔IR (+) group, 114 cases〕 and those without〔IR (-) group, 339 cases〕 grouped by the level of homeostasis model assessment of insulin resistance (HOMA-IR) . And the correlation between each index and HOMA-IR was analyzed. Multivariate Logistic regression analysis was used to explore the influencing factors of IR in PCOS patients with normal BMI. Results Compared with IR (-) group, IR (+) group had higher average levels of BMI, waist circumference (WC) , waist-to-hip ratio (WHR) , systolic blood pressure (SBP) , free androgen index (FAI) , fasting plasma glucose (FPG) , fasting insulin (FINS) , total cholesterol (TC) , triacylglycerol (TG) , low-density lipoprotein cholesterol (LDL-C) and apolipoprotein B (ApoB) , and lower average levels of serum AMH, sex hormone-binding globulin (SHBG) , total bilirubin (TBiL) , direct bilirubin (DBiL) , creatinine, β2 microglobulin, calcium, phosphorus, magnesium, sodium, and chloride (P<0.05) . Correlation analysis showed that TG, WC, BMI, ApoB, TC, FAI, WHR, SBP, and LDL-C had positive correlation with HOMA-IR (P<0.05) . Serum DBiL, TBiL, SHBG, phosphorus, chloride, sodium, creatinine, AMH, magnesium, FT, calcium, and β2 microglobulin was negatively correlated with HOMA-IR (P<0.05) . Multivariate Logistic regression analysis showed that BMI〔OR=1.291, 95%CI (1.067, 1.561) 〕, WC〔OR=1.042, 95%CI (1.004, 1.081) 〕, FAI〔OR=1.092, 95%CI (1.022, 1.167) 〕, TG〔OR=1.902, 95%CI (1.401, 2.583) 〕, AMH〔OR=0.956, 95%CI (0.918, 0.997) 〕, TBiL〔OR=0.871, 95%CI (0.789, 0.962) 〕, phosphorus〔OR=0.209, 95%CI (0.067, 0.651) 〕were influencing factors for IR in PCOS patients with normal BMI (P<0.05) . Conclusion The incidence of IR in PCOS patients with normal BMI was 25.16% (114/453) , whose risk increased with the elevation in BMI, WC, FAI and TG, and the reduction in serum AMH, TBiL, and phosphorus.